A portable medical monitoring device Part III - Teo, Adeline Wei Ling (2014)
In the recent years, raised in blood pressure have seen taken the life of 7.5 million people worldwide which accounted for 12.8% in total death according to World Health Organization (WHO). It has also shown that blood pressure level can cause vascular weakness, heart attack , stroke ,tissue and organ damage from narrowed and blockage arteries. Some of the factors include lacked of exercise, consumed high level of salty food, family history, smoking and drinking. Thus monitoring of blood pressure is very important. Hence the main objective is to develop a Windows application that communicate with a blood pressure monitoring device and receives medical data using the Bluetooth Serial Port Profile (SPP) and transmits the data to a remote server via the internet to improve the effectiveness and efficiency of recording and retrieving medical record for healthcare provider and patient in replacing the old traditional method of hand written on paper. In addition, allow the patient to measure their blood pressure from home and send it over to the remote server, which allow the healthcare provider to monitor it from the clinic. Moreover, with a graphical chart allow monitoring of blood pressure more easy and an enquiry platform to allow easy communication between patient's home and the clinic.